(untitled) (Journal of Computational Mathematics, 2004)
In this paper, the authors present a locking-free scheme of the lowest order nonconforming rectangle finite element method for the planar elasticity with the pure displacement boundary condition. Optimal order error estimate, uniformly for the Lamé constant λ(0,∞) is obtained.